Quantification of redox thermodynamics shifts within coacervates - Gala Rodriguez; Nicholas B. Watkins; Xagros Faraji; Elizabeth Lee; Lior Sepunaru (Proceedings of the National Academy of Sciences, 2025)
Coacervates are suggested to be viable protoenzymes due to their propensity to act as catalytic microreactors for biochemical reactions. However, the mechanism by which they alter reaction thermodynamics remains unclear. While extensive research has been conducted displaying the ability of coacervates to compartmentalize a wide variety of reactants, products, and catalysts, insight into how reactant, transition state, and product energies are altered within the droplet continues to be an active area of research. One promising strategy for investigating the thermodynamics and kinetics within the coacervate phase is temperature-dependent electrochemistry, which enables the extraction of reaction entropy, enthalpy, and Gibbs energy. In this work, we use ferri/ferrocyanide, a well-behaved redox couple that has been proposed to be an essential oxidizing agent in prebiotic Earth, to investigate the microenvironment created by the coacervation of poly-L-lysine and polyuridylic acid. We observe an oxidative shift upon partitioning into the coacervates, which temperature-dependent experiments reveal is due to a 40 J/mol K and an 8 kJ/mol increase in reaction entropy and enthalpy, respectively. We attribute the change in entropy to a highly structured water hydrogen-bonding network within the droplets and, subsequently, around the redox probe. Further, we reveal via in situ Raman measurements that the change in reaction enthalpy is due to the destabilization of the product, ferrocyanide, within the ionic coacervate phase.